Diffie-Hellman Key Exchange Based on Block Matrices Combined with Elliptic Curves - Hadi , Hiba Hilal; Neamah, Ammar Ali (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Various techniques were used to improve and propose cryptographic systems based on elliptic curves. In particular, the Diffie-Hellman key exchange protocol is widely used in most of these systems. In this work, we introduce an efficient approach based on the block matrices integrated with elliptic curves to increase the security of this protocol. With the new system, we can reduce key size without expanding the underlying elliptic curve. Therefore, the proposed protocol security will be more intractable since it will need to solve the Elliptic Curve Discrete Logarithm Problem more than once based on the chosen block matrices compared with the original protocol.